Simplified Motion Control of a Vehicle manipulator for the Coordinated Mobile Manipulation - Mishra, Swati; Mohan, Santhakumar; Vishvakarma, Santosh Kumar (Defence Science Journal, 2020)
This paper considers a resolved kinematic motion control approach for controlling a spatial serial manipulator arm that is mounted on a vehicle base. The end-effector’s motion of the manipulator is controlled by a novel kinematic control scheme, and the performance is compared with the well-known operational-space control scheme. The proposed control scheme aims to track the given operational-space (end-effector) motion trajectory with the help of resolved configuration-space motion without using the Jacobian matrix inverse or pseudo inverse. The experimental testing results show that the suggested control scheme is as close to the conventional operational-space kinematic control scheme.